FRAUD MINIMIZATION IN VIEW OF GOOD CORPORATE GOVERNANCE, OPERATIONAL EFFECTIVENESS AND RISK MANAGEMENT - Zulhawati; Meiliyah Ariani; Minarni, Sarida (Universitas prof. Dr. Moestopo (Beragama), 2023)
Risk management disclosure is one of the company's responsibilities and is part of the management to reduce fraud Theavailability of good management in directing and regulating risk is the basis for each banking company as an effort to minimize bankruptcy To run a banking company running well, you should also carry out the rules of governance or good corporate governance well. The purpose of this study is to determine the effect of good corporate governance, operational effectiveness and risk management on fraud disclosure in employees working at Bank Negara Indonesia Harmoni Jakarta Branch. The research samples used in this study were 100 samples. The data used in this study are primary data. The analysis method in this study uses descriptive statistical tests, data quality tests, classical assumption tests, hypothesis tests and determination coefficient tests using the SPSS program. Based on the results in this study, it shows that good corporate governance and effectiveness do not produce positive and insignificant influences. Meanwhile, risk management has a positive and significant effect. This means that risk management is very important and influential in the disclosure of fraud in banking companies.